PELATIHAN PENGEMBANGAN POTENSI DESA WISATA BERBASIS EKOWISATA DAN PENGETAHUAN GUIDE DI PATEMON GUNUNGPATI SEMARANG - Suwarti; Dyah Palupiningtyas (Jurnal Pengabdian Masyarakat Waradin, 2021)
Development of Village Potential in tourism in Patemon Village, Gunungpati District, Semarang, as well as the implementation of community service by several lecturers who have knowledge and skills about tourism. This activity was in the form of socialization about the Potential of Tourism Village based on Ekowista and Guide. The main objective of this activity is to help the people of Patemon Village, Gunungpati District, Semarang City, in order to develop the potential of their village for tourism activities. As well as providing benefits in the form of Training and Skills related to the Tourism Sector based on the Tourism Law Number 10 of 2009 in Chapter I article 1. The method used is Participatory Action Research (PAR) Analyzing the potential of Tourism Villages, in collaboration with UPRRID KKN Students, village potential based on maps, thus the principle of developing village potential as a tourist destination location through FGD of Village potential for the development of Leading Ecotourism. With the principle of making tour packages by practicing Guide training, this is the concept of Tourism Promotion and its marketing